Learning disruptions during the COVID-19 pandemic: Evidence from household surveys in Southeast Asia - Angelica Maddawin; Peter J. Morgan; Albert Park; Daniel Suryadarma; Trinh Quang Long; Paul Vandenberg (Asian Development Bank Institute (ADBI), 2024)
We study children's access to remote learning when schools were closed during the COVID-19 pandemic and their parents' perceptions about learning progress in seven Southeast Asian countries. This is the first regional analysis to systematically document students' access to remote learning based on survey data and to investigate how school closures and remote learning access affected children's learning progress. The results are based on survey responses from 2,200 households. We find that 80% of the respondents felt that their children's learning progress was slower during school closures than it would have been with in-person schooling. Slightly less than half of all children experienced very little or no learning progress. Three characteristics were strongly correlated with learning progress: first, boys were more likely than girls to experience very little or no progress; second, children from households in the top 30% of the income distribution were more likely to progress at the same rate as in in-person classes than children from lower-income households; third, comparing the different remote learning modes, internet-based learning or multiple learning modes provided children with a better chance of maintaining learning progress than other single modes.
Keywords: I21; I28; 330; COVID-19; school closure; learning loss; Southeast Asia